The brain that wouldn't die - Green, Joseph, 1928-1999; Evers, Jason, 1922-2005; Rex Carlton Productions (Firm); Cinetel Films ([Los Angeles, CA] : Rex Carlton Productions, 1962)
Dr. Bill Cortner is a brilliant young surgeon who experiments illegally with the bodies and minds of fellow humans. When his fiancee is decapitated in a freak accident, he tries to transplant her still living head and brain to another body.
Originally released as a motion picture in 1962
Herb Evers, Virginia Leith, Leslie Daniel.
Cinematographer, Stephen Hajnal; editor, Marc Anderson.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2016).
Keywords: Brain -- Experiments -- Drama; Surgeons -- Drama; Human experimentation in medicine -- Drama; Traffic accident victims -- Drama; Horror films; B films; Mad scientist films; Feature films; Fiction films; Internet videos; Streaming video